The influence of location and ambient conditions on repurchase intention at Dendivila Coffee Saniangbaka Solok - Vina Yuniar; Pasaribu (Journal of Multidimensional Management, 2025)
This study examines how location and ambient conditions, treated as core servicescape cues, shape repurchase intention at a lakeside coffee shop in Solok, Indonesia. Using a quantitative, causal-associative design, we surveyed customers with five-point Likert measures and analyzed the data with multiple linear regression (n = 118; purposive sampling). Measurement quality checks covered normality, heteroscedasticity, and multicollinearity diagnostics, and model adequacy was assessed with F-tests and adjusted R². Both predictors were significant: location (β = 0.389, p < .001) and ambient conditions (β = 0.330, p < .001). The model explains 41.4% of the variance in repurchase intention (adjusted R² = 0.414; F(2,115) = 42.40, p < .001), indicating medium practical effects. The contribution is the contextualization of servicescape effects in a peri-urban, view-centric setting where access, visibility, thermal comfort, and music audibility can fluctuate with weather and visitor density. From a managerial perspective, prioritizing clear access and parking, improving pedestrian visibility, regulating temperature and airflow, and calibrating music by time of day are actionable levers to stabilize repeat patronage. Future research should incorporate additional servicescape dimensions (for example, layout and signage), test mediation by satisfaction or perceived value, and validate the measurement model using confirmatory factor analysis.